Detection and spread of Phytophthora austrocedri within infected Juniperus communis woodland and diversity of co‐associated Phytophthoras as revealed by metabarcoding. Issue 3 (17th May 2020) - Riddell, Carolyn E.; Dun, Heather F.; Elliot, Matt; Armstrong, April C.; Clark, Mhairi; Forster, Jack; Hedley, Pete E.; Green, Sarah
Abstract: Phytophthora austrocedri is a recently invasive soilborne pathogen which is causing widespread mortality of Juniperus communis in northern Britain. The pathways by which a single genotype of P. austrocedri has spread to infect such a geographically dispersed range of woodland sites within a relatively short timeframe are unknown. This study examined the detectability of P. austrocedri in soil and water within infected J. communis woodland using qPCR to gain a better understanding of the pathogen's key mechanisms of spread. A Phytophthora metabarcoding method was also applied to investigate the wider diversity of Phytophthora species present in water at one of the sites. qPCR analyses of P. austrocedri in soil samples at a J. communis woodland exhibiting low‐to‐moderate levels of disease suggested a slow natural spread of the pathogen in soil, requiring high moisture conditions. However, the ubiquity of P. austrocedri DNA in soil samples collected across a heavily infected J. communis site suggests that once established at a site the pathogen can be spread readily in soil locally, most likely vectored by animal movements and/or human activities. The hypothesis that P. austrocedri is aerially transmitted in rainwater was not adequately proven, and an alternative hypothesis for the widespread distribution of the pathogen on J. communis in northern Britain is presented. Metabarcoding identified DNA from a diverse range of Phytophthora species in river and rainwater samples although the main target pathogen, P. austrocedri, was not amplified which disagreed with some of the qPCR findings. Possible reasons for this are discussed.